MORPHOMETRIC PARAMETERS OF INTIMA-MEDIA THICKNESS AND DIAMETERS OF CAROTID AND FEMORAL ARTERIES OF THE DEAD, SUFFERED ARTERIAL HYPERTENSION - Danovskaya, E.V.; YabluchanskіyN.I.; RemnіоvaN.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
This paper presents the result of morphometric parameters of intima, media and diameters of carotid and femoral arteries according to biopsy materials from patients, suffered from arterial hypertension(AH). The conclusion has been made that structural changes of vascular wall in the presence of AH in carotid arteries is occur to a greater extent, due to thickening of intima and in femoral arteries- due to media, but for all that their sizes practically did not differ.